2018
DOI: 10.1088/1748-9326/aaafda
|View full text |Cite
|
Sign up to set email alerts
|

How well do meteorological indicators represent agricultural and forest drought across Europe?

Abstract: Drought monitoring and early warning (M&EW) systems are an important component of agriculture/silviculture drought risk assessment. Many operational information systems rely mostly on meteorological indicators, and a few incorporate vegetation state information. However, the relationships between meteorological drought indicators and agricultural/silvicultural drought impacts vary across Europe. The details of this variability have not been elucidated sufficiently on a continental scale in Europe to inform dro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
125
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(139 citation statements)
references
References 42 publications
14
125
0
Order By: Relevance
“…Previous works on agricultural drought analysis also selected SPI‐3 (i.e., Bachmair et al, ; Lim et al, ; Sigdel & Ikeda, ), supporting our decision. For example, Bachmair et al () performed a correlation analysis between SPI at different time scales and remote sensing‐based vegetation indices for Europe. They showed that short accumulation periods of SPI (in particular three months) relate well to crop vegetation stress in most cases.…”
Section: Resultssupporting
confidence: 76%
“…Previous works on agricultural drought analysis also selected SPI‐3 (i.e., Bachmair et al, ; Lim et al, ; Sigdel & Ikeda, ), supporting our decision. For example, Bachmair et al () performed a correlation analysis between SPI at different time scales and remote sensing‐based vegetation indices for Europe. They showed that short accumulation periods of SPI (in particular three months) relate well to crop vegetation stress in most cases.…”
Section: Resultssupporting
confidence: 76%
“…They also found that a higher percentage of forests from different biomes across the world correlated better with the SPEI than with the SPI. For its part, Bachmair et al [50] assessed the relationship between meteorological indicators and forests in Europe, suggesting slight differences between the SPEI and SPI. Nonetheless, they noted that-at shorter time scales-the SPEI shows a stronger response in the forests of southern Europe, a result that is in agreement with the findings of our study.…”
Section: Discussionmentioning
confidence: 99%
“…To accomplish this task, we linked seven widely used drought indices: Standardized Precipitation Evapotranspiration Index (SPEI), Standardized Precipitation Index (SPI), Standardized Palmer Drought Severity Index (SPDSI), and four Palmer-related drought indices (Palmer Drought Severity Index (PDSI), Palmer Hydrological Drought Index (PHDI), Palmer Z-Index (Z), and Palmer Modified Drought Index (PMDI)) with climatic, NDVI, and dendrochronological data for the IP and the Balearic Islands for the period 1981-2015. As a result we should be able to assess the validity of these drought indices to assessing and monitor the impacts of drought on forest growth and vitality [48][49][50].…”
Section: Introductionmentioning
confidence: 99%
“…Drought can be characterized based on impact information from socioeconomic sectors (Porter & Semenov, ), natural ecosystems (Bachmair, Tanguy, Hannaford, & Stahl, ; Camarero, Gazol, Sangüesa‐Barreda, Oliva, & Vicente‐Serrano, ), crops (Peña‐Gallardo et al, ; H. Wang et al, ), and hydrological systems (Barker, Hannaford, Chiverton, & Svensson, ; Peña‐Gallardo et al, ). Nevertheless, drought is more frequently quantified using meteorological variables that can be observed or modeled (Mukherjee et al, ).…”
Section: Introductionmentioning
confidence: 99%